Self-Starting Soliton-modelocked Femtosecond Cr(4+):YAG Laser Using an Antiresonant Fabry-Perot Saturable Absorber - Leuchs, Gerd; et al. (Applied Physics B-Lasers and Optics, 1997)
We set up a self-starting passively modelocked femtosecond Cr(4+):YAG laser using a low-finesse antiresonant Fabry-Pérot saturable absorber (A-FPSA). Stable transform-limited pulses were produced without the critical cavity alignment necessary for Kerr lens modelocking. We achieved 114-fs pulses with 94 mW output power at the telecommunication wavelength 1.5 μm. The pulse formation is demonstrated to be due to soliton modelocking. At higher intracavity energy multiple pulsing was observed and is explained by the saturation behaviour of the A-FPSA. In the multipulsing regime a pulse width as short as 95 fs and an averaged output power of up to 395 mW have been obtained. © Springer-Verlag 1997.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.selfst